2024
DOI: 10.1101/2024.04.15.589582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The response to single-gene duplication implicates translation as a key vulnerability in aneuploid yeast

H. Auguste Dutcher,
James Hose,
Hollis Howe
et al.

Abstract: Aneuploidy produces myriad consequences in health and disease, yet models of the deleterious effects of chromosome amplification are still widely debated. To distinguish the molecular determinants of aneuploidy stress, we measured the effects of duplicating individual genes in cells with varying chromosome duplications, in wild-type cells and cells sensitized to aneuploidy by deletion of RNA-binding protein Ssd1. We identified gene duplications that are nearly neutral in wild-type euploid cells but significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 109 publications
1
14
0
Order By: Relevance
“…Trisomy 21 in humans and chromosome amplification in sensitized W303 yeast is associated with increased protein aggregation, although the source of proteostasis stress is not known. We previously showed that wild aneuploid yeast strains do not show signs of proteostasis dysfunction unless stressed by SSD1 deletion or treated with translational inhibitor NTC 13,22 . Here we found that aging also induces protein aggregation in wild aneuploids: at 7 days of culturing, 50-70% of aneuploids with extra Chr4 or Chr12 harbored foci of protein disaggregase Hsp104, compared to ~5% of euploid cells.…”
Section: Proteostasis Stress Is Alleviated By Duplication Of Rqc or U...mentioning
confidence: 99%
See 4 more Smart Citations
“…Trisomy 21 in humans and chromosome amplification in sensitized W303 yeast is associated with increased protein aggregation, although the source of proteostasis stress is not known. We previously showed that wild aneuploid yeast strains do not show signs of proteostasis dysfunction unless stressed by SSD1 deletion or treated with translational inhibitor NTC 13,22 . Here we found that aging also induces protein aggregation in wild aneuploids: at 7 days of culturing, 50-70% of aneuploids with extra Chr4 or Chr12 harbored foci of protein disaggregase Hsp104, compared to ~5% of euploid cells.…”
Section: Proteostasis Stress Is Alleviated By Duplication Of Rqc or U...mentioning
confidence: 99%
“…Among the most intriguing on the list of 37 genes was RQC1, a component of the RQC pathway that resolves stalled ribosomes 36,37,76 . This was interesting because aneuploid strains are sensitive to translational inhibitor nourseothricin (NTC) that binds the ribosome to disrupt translation 13,22,[77][78][79] . Given that translation defects increase with cellular age [44][45][46] , these results raised the possibility that chromosome duplication induces defects in the RQC pathway.…”
Section: A Genetic Screen For Lifespan Extension Implicates the Rqc P...mentioning
confidence: 99%
See 3 more Smart Citations